In a world with many targets, one-dimensional target indicators will always be bypassed - Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
It is striking that economists in particular firmly believe in the benefits of rule-binding, even though this belief runs counter to the standard assumption of economic theory that we humans are self-interested and therefore extremely resourceful when it comes to circumventing inconvenient government regulations, e.g. taxes. In Public Choice Theory, politicians are even assumed to have nothing but self-interest as their guiding motive for action. Why then, in this world of thought, should ultra-self-interested politicians of all people adhere to simple rules such as the debt brake instead of bypass them, if - as is also assumed in this model world - all that matters to them is short-term electoral success, for which government debt can be helpful.
Keywords: B10; B20; K00; P16; 330; rule-binding; Champbell; Goodhart's Law; Hobbes